Wakaf Collection and Management Strategy at Al Ruhamaa' Bogor Wakaf Institution - Al Muharram, Muhammad Shiddiq; Beik, Irfan Syauqi; Irfany, Mohammad Iqbal; Haq, Daffa Aqomal (SMART Insight, 2024)
History has recorded that the use of waqf in the golden age of Islam was able to drive the country's economy well. Therefore, a waqf management scheme is needed that has an optimal impact on people's welfare. This study aims to identify aspects of strengths, weaknesses, opportunities, threats, and strategic priorities in the collection and management of waqf at Al Ruhamaa' Waqf Institution. The method used in this study is the Analytical Network Process (ANP) with the Strength-Weakness-Opportunity-Threat (SWOT) network. The results of this study indicate that avoiding aspects of weakness is a top priority in collecting and managing waqf at Al Ruhamaa' Waqf Institution. The most influential aspects of strengths, weaknesses, opportunities and threats, namely having institutional legality, branding and marketing that are not optimal, the potential for large waqf, and the trust of different waqif candidates. The most priority strategy to implement is promoting the waqf program through the latest marketing channels.